Spectral Characterization and Crystal Structure of 1,2-Bis-(1H-benzimidazol-2-yl)-ethane Dihydrochloride - Aydin Tavman; Cigdem Sayil (Journal of Chemistry)
The crystal structure of 1,2-bis-(1H-benzimidazol-2-yl)-ethane dihydrochloride (1) was determined by X-ray diffraction at room temperature. The structure of 1 was also characterized by mass, elemental analysis, FT-IR, and NMR spectroscopy techniques. The title compound crystallizes in triclinic system and space group P-1, a=7.1350, b=9.6299(1), c=15.3340(7) Å, α=80.67(2),β=79.66(2),γ=68.395(11)∘, V=958.33(10) Å3, Z=2. Owing to the anti conformations of –CH2– groups, the entire molecule is relatively flat. H1-NMR spectra of 1 show AA′XX′ system characteristics.